PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP PENGUNGKAPAN INTERNET FINANCIAL AND SUSTAINABILITY REPORTING (IFSR) (Studi pada Perusahaan yang Terdaftar di Bursa Efek Indonesia) - Ayu Puspitaningrum; Arum Prastiwi (Jurnal Ilmiah Mahasiswa FEB, 2012)
The purpose of this study is to find empirical evidence of firm’s characteristics effect on the disclosure of Internet Financial and Sustainability Reporting (IFSR). Firm characteristics are identified as firm size, profitability, leverage, and industry type. The population in this study are all of 429 Indonesian companies listed in Indonesian Stock Exchange (IDX) in period 2011. This study selected 182 companies by using nonprobability random sampling (purposive sampling method). The technique for examining hyphotesis is using logistic regression analysis. The result indicates that firm size, profitability, and industry type influence disclosure of IFSR. In addition, leverage have no effect on the disclosure of IFSR. Keyword:        Internet Financial and Sustainability Reporting (IFSR), firm size, provitability, leverage, and industry type